2013
DOI: 10.4103/2277-9175.114194
|View full text |Cite
|
Sign up to set email alerts
|

Results of treatment of acute myeloid leukemia in central part of Iran

Abstract: Background:Acute myeloid leukemia (AML) is the most common type of leukemia. In this study, outcome of intensive chemotherapy in patients treated in a large urban public university hospital in a developing country was investigated.Materials and Methods:The records of all patients treated for AML with 3 + 7 protocol from 2002 to 2010 were analyzed.Results:Among 95 patients, 34 (35.8%) were female and 61 (64.2%) were male patients. Patients’ median age was 37 years, ranging 15-68 years. Complete remission (CR) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
2
2
Order By: Relevance
“…Furthermore, the study of Allahyari et al was performed on various subtypes of AML rather than only APL. In a study on 95 AML patients in Iran, median overall survival was reported 13 months, with one-year and two-year survival rates of 51% and 26% respectively (15). This was considerably lower than the survival observed in our study which may be due to the heterogeneity of AML subtypes in the before mentioned study.…”
Section: Discussioncontrasting
confidence: 86%
“…Furthermore, the study of Allahyari et al was performed on various subtypes of AML rather than only APL. In a study on 95 AML patients in Iran, median overall survival was reported 13 months, with one-year and two-year survival rates of 51% and 26% respectively (15). This was considerably lower than the survival observed in our study which may be due to the heterogeneity of AML subtypes in the before mentioned study.…”
Section: Discussioncontrasting
confidence: 86%
“…Our study findings are similar to previously reported data. In contrast to our results, a few studies found NPM1 mutations incidence as low as 4.2%, 6% and 8% [22,23].…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, t(15;17) (q22;q21) had the most frequency in AML patients (37.7%). A study reported that the 1-and 2-year survival rate for AML patients was 51% and 26%, respectively (Ashrafi et al, 2013). Two studies (Juliusson et al, 2009;Alibhai et al, 2009), reported 3-year survival rates was between 9-10% and 5-year survival was 3-8% in patients≥60 years, compared with 5-year survival rates of up to 50% for younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…Patients in other research (Byrd et al, 1998), had a median age of 64 years (range, 16-79 years), 50% male. Three studies in Iran reported that: In study 1 (Ashrafi et al, 2013), patients' median age was 37 years (range, 15-68 years), 64.2% were male. In study 2 (Ayremlou et al, 2012), the mean age in AML patients was 44.7 years that 56.3% were male.…”
Section: Discussionmentioning
confidence: 99%